Taxpayer Compliance of MSME: The Role of Tax Knowledge, Tax Office Service Quality, and Trust in the Government - Sulistyowati; Rusli, Devvy; Chusnah, Flourien Nurul; Supriati, Diana; Annisa, Annisa (Santoso Academy Network, 2024)
This research aims to determine the influence of the role of tax knowledge, tax service quality, and trust in the government on Kemayoran District MSME taxpayer compliance. The method used in this research is the data collection method through a questionnaire which is measured using a Likert scale. The sampling method uses a purposive sampling technique with the criteria of MSME actors in the Kemayoran District area and those who have an income of >500 million per year. This research is quantitative research. The results of this research state that knowledge of taxation influences the compliance of Kemayoran District MSME taxpayers, the quality of tax service does not influence the compliance of Kemayoran District MSME taxpayers, and trust in the government does not influence the compliance of Kemayoran District MSME taxpayers.